2019
DOI: 10.21608/ejh.2019.47568
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Omega-3 on Energy Drinks - Induced Pancreatic Toxicity in Adult Male Albino Rats

Abstract: Background: The world wide increasing popularity of the energy drinks and the lack of information about their possible hazardous effects on health is a matter of controversy and research. The aim of this study is to assess the histological and histochemical effects of energy drinks on the pancreas of adult male albino rats and the possible protective effect of omega-3. Material and Methods: Fifty adult male albino rats were randomly divided into 4 groups. First group is control. Second group (Omega-3 treated) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the present study, the gross morphological study of the lungs exposed to formaldehyde revealed irregular convoluted surfaces of most lungs, increased congestion, and appearance of masses. These results are in agreement with previous studies whereas rats were exposed to formaldehyde for different durations which showed congestion in most lobes and focal pneumonic organization (Khaliq and Tripathi, 2009;Afrin et al, 2016;El Desouky et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the gross morphological study of the lungs exposed to formaldehyde revealed irregular convoluted surfaces of most lungs, increased congestion, and appearance of masses. These results are in agreement with previous studies whereas rats were exposed to formaldehyde for different durations which showed congestion in most lobes and focal pneumonic organization (Khaliq and Tripathi, 2009;Afrin et al, 2016;El Desouky et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Group III (Formaldehyde and Omega-3 group): included 10 adult male rats subjected to formaldehyde inhalation as Group II and orally administered with 300 mg/kg/day of Omega-3 for 4 weeks using sterilized rats stomach tube. (El Desouky et al, 2019). After 24 hours from the last dose, rats were anesthetized using ether inhalation, carefully dissected, and the specimens from the lung and the left ventricle of the heart were taken.…”
Section: Experimental Designmentioning
confidence: 99%
“…Majority of these effects were reversible after the energy drink was stopped, according to the current study. El Desouky et al [34] found similar results when they looked at the histological and histochemical effects of energy drinks on the pancreas of adult albino rats. This was reinforced by Akande and Banjoko [17] , who elucidated that the harm caused by excessive use of caffeinated energy drinks is reversible, as evidenced by blood chemistry analysis and histological examination of the organs of recovery group animals.…”
Section: Discussionmentioning
confidence: 69%
“…Sadowska (26) and El Desouky et al (27) mentioned that high concentration of sugar besides niacin in the energy drink may alter carbohydrate metabolism following their intake leading to increscent in the level of glucose and insulin in the blood accompanied by insulin resistance. This may explain the reason of the enlarged size of islets following consumption of low dose of red bull as a compensatory mechanism to reduce the high level of blood sugar by secreting more insulin.…”
Section: Discussionmentioning
confidence: 99%